Advancing Activism Through Academic Scholarship: What's in a Name (Revisited). (3rd July 2022) - González, Gerardo M.; Rios, Francisco
Abstract : This article discusses an effort in the early 1990s to question the naming of campus edifices to recognize California state Senator William Craven (1973–1998), who made public statements considered anti-Latino while in office. During that period, there were very few movements to rename campus landmarks. This article analyzes one of these early movements and the personal and practical implications for the authors, who were proponents of the movement. We focus on how academic writing can be used to advance the project of educational justice, even if progress is slow and at times delayed.